1986
DOI: 10.1901/jeab.1986.45-5
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Pattern of Unconstrained Drinking: Rats' Responses to Inversion and Identity Constraints

Abstract: Rats obtained all of their water by licking a metal tube during a series of daily 1-hour sessions. When the tube was freely available throughout, each rat showed the classic temporal pattern of unconstrained drinking: As the session progressed, drinking bouts generally grew shorter and pauses grew longer. In subsequent sessions the tube was opened and closed independently of the rat's behavior, on a schedule that gave the rat a chance to duplicate the exact inverse of its unconstrained baseline pattern. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…In paired-baseline, 85% of the total water intake occurred within the first 10 min of the session. These results are typical for the temporal distribution of water intake for deprived rats (Allison et al, 1986; Hatton & Bennett, 1970; Rolls & Rolls, 1982; Gawley et al, 1986). The current constraints reduced this proportion to approximately 25% within the first 10-min bin and forced the rats to consume a larger proportion of water over the remainder of the session.…”
Section: Methodssupporting
confidence: 56%
See 2 more Smart Citations
“…In paired-baseline, 85% of the total water intake occurred within the first 10 min of the session. These results are typical for the temporal distribution of water intake for deprived rats (Allison et al, 1986; Hatton & Bennett, 1970; Rolls & Rolls, 1982; Gawley et al, 1986). The current constraints reduced this proportion to approximately 25% within the first 10-min bin and forced the rats to consume a larger proportion of water over the remainder of the session.…”
Section: Methodssupporting
confidence: 56%
“…It may be that the instigation for drinking is tightly related to the baseline temporal distribution and that local disruptions of this response characteristic effectively reduce the overall instigation for drinking. Allison et al (1986), however, reported that rats maintained baseline water intake when the opportunity to drink was the exact reverse of the baseline temporal pattern of drinking. However, these results are difficult to compare because the rats in that study also had access to food in the experimental chamber, which might have stimulated postprandial drinking.…”
Section: Underdrinking Effectmentioning
confidence: 98%
See 1 more Smart Citation
“…When both models failed in Experiment 3, we were dismayed by the failure but pleased with the power of the test. A feature that the two models have in common is their concern with behavioral totals, rather than the path the individual follows in generating those totals (Allison, Moore, Gawley, Mondloch, & Mondloch, 1986). Perhaps better models can be developed with the help of a more detailed account of the behavioral patterns displayed with both spouts were freely available.…”
Section: Paired Baseline Patterns and Totals: Experiments 1–3mentioning
confidence: 99%
“…For example, if the contingent requirement is defined in terms of the number of licks at a water spout, the rat may achieve its baseline water intake before reaching its baseline number of water licks (Buxton & Allison, 1990). Symmetrically, if the contingent requirement is defined in terms of volumetric intake, the rat may achieve its baseline number of water licks before reaching its baseline intake (Allison & Buxton, 1992; see also Allison, Moore, Gawley, Mondloch, & Mondloch, 1986). In any event, the suppression of both responses under a nondeprivation schedule suggests that response deprivation may not be sufficient for reinforcement.…”
mentioning
confidence: 99%